2016
DOI: 10.1038/nmicrobiol.2016.65
|View full text |Cite|
|
Sign up to set email alerts
|

The abundant marine bacterium Pelagibacter simultaneously catabolizes dimethylsulfoniopropionate to the gases dimethyl sulfide and methanethiol

Abstract: Marine phytoplankton produce ~109 tons of dimethylsulfoniopropionate (DMSP) per year1,2, an estimated 10% of which is catabolized by bacteria through the DMSP cleavage pathway to the climatically active gas dimethyl sulfide (DMS)3,4. SAR11 Alphaproteobacteria (order Pelagibacterales), the most abundant chemoorganotrophic bacteria in the oceans, have been shown to assimilate DMSP into biomass, thereby supplying this cell’s unusual requirement for reduced sulfur5,6. Here we report that Pelagibacter HTCC1062 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 59 publications
(97 reference statements)
11
155
1
Order By: Relevance
“…The implication is that acetaldehyde is a significant component of labile DOM. In the experiments described here, acetaldehyde oxidation activity was expressed in SAR11 cells without induction, in agreement with other research indicating that these cells have limited transcription regulation, particularly of genes for carbon catabolism (Giovannoni et al ; Sun et al ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The implication is that acetaldehyde is a significant component of labile DOM. In the experiments described here, acetaldehyde oxidation activity was expressed in SAR11 cells without induction, in agreement with other research indicating that these cells have limited transcription regulation, particularly of genes for carbon catabolism (Giovannoni et al ; Sun et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Rates of acetaldehyde incorporation and oxidation decreased after 3–8 h, which is typical of saturation. We do not know the cause of these apparent saturation kinetics for acetaldehyde, but in experiments with other substrates we have found that hours are required for intracellular concentrations to stabilize at their maxima (Sun et al ). Alternatively, it is possible that a decrease in the cells’ activities over time occurred, but this explanation seems less likely to us because many of Pelagibacter's metabolic pathways are constitutively expressed.…”
Section: Resultsmentioning
confidence: 97%
“…The extent of this pathway in methionine salvage – likely to have been of prime importance in the early times of life, before the dioxygen rise – is, however, expected to be moderate, as methanethiol is often exported as waste rather than recovered for anabolism. This is shown for example in the metabolism of Pelagibacter ubique (Sun et al ., ).…”
Section: Alternate Fates Of Mtru‐1‐p and Its By‐productsmentioning
confidence: 97%
“…DMSP is cleaved to DMS and acrylate by enzymes collectively termed DMSP‐lyases, present within coral zooxanthellae, marine microalgae, and coral‐associated and free‐living bacteria (Alcolombri et al, 2015; Bullock et al, 2017; Raina et al, 2009; Sun et al, 2016). DMS/P and acrylate rapidly scavenge these ROS forming DMSO, which may be further oxidized by ROS to MSA (Sunda et al, 2002).…”
Section: Introductionmentioning
confidence: 99%